Anti-inflammatory and antioxidant activities of 4-allylpyrocatechol and its derivatives with molecular docking and ADMET investigations - Annavarapu, T.; Kamepalli, S.; Kondala, S.K.; Kotra, V.; Challa, S.R.; Rudrapal, M.; Bendale, A.R. (KU Publ., 2022)
Abnormal production of pro-inflammatory mediators and generation of reactive oxygen species (ROS) play a key role in the development and progression of various human disorders. The study aims to investigate the in vitro anti-inflammatory and antioxidant activity of 4-allyl pyrocatechol (4-APC) and its derivatives (APC-1 and APC-2) by albumin denaturation and 1,1-Diphenyl-2-picrylhydrazyl (DPPH) methods, respectively. Also, the test compounds are studied in silico for their inhibitory potential against the pro inflammatory and oxidative markers (calpain, FAAH, and TNF-α) via molecular docking. The compounds have exhibited appreciable in vitro anti-inflammatory and antioxidant activities. The APC-2 compound has demonstrated significant anti-inflammatory and antioxidant activity (percentage inhibition = 69±0.76 and 77.05±0.92, respectively, at 100 μg/ml) compared to the standard drugs, aspirin and ascorbic acid (percentage inhibition = 82±0.83 and 92.35±0.75, respectively, at 100 μg/ml). The docking study has showed that APC-2 significantly inhibited calpain (PDB ID: 2R9C), FAAH (2WJ1) and TNF-α (2AZ5) inflammatory markers. The drug-likeness, bioactivities, ADME profile (pharmacokinetic) and toxicity properties have also been determined using online tools (Molinspiration, pkCSM, SwissADME, PreADMET). The test compounds have showed acceptable drug-likeness, bioactivity score, ADME and toxicity properties. Finally, we conclude that the 4- allylpyrocatechol and its derivatives can be used as lead molecules for their further development as therapeutically useful anti-inflammatory agents.
4-Аллилпирокатехиннің қабынуға қарсы және антиоксиданттық белсенділігін және оның туындыларын молекулалық докинг пен ADMET арқылы зерттеу
Исследование противовоспалительной и антиоксидантной активности 4-аллилпирокатехина и его производных методами молекулярного докинга и ADMET
Keywords: pyrocatechol; anti-inflammatory; antioxidant; lead molecule; inflammatory markers; calpain; FAAH; TNF-α; docking; ADMET